Congenital stricture of the vestibulo‐vaginal fold in a mare with normal karyotype. (11th December 2020) - Guimarães, T.; Oliveira, C.; Crespo, J.; Porto, B.; Cunha, R.; Rocha, A.
Summary: A diagnosis of congenital stricture of the vestibulo‐vaginal fold was reached in an 11‐year‐old mare without previous reproductive records, during a breeding soundness examination. The mare had an annular stricture of the vestibule–vaginal fold that did not allow palpation or vaginoscopic visual examination of the anterior portion of the vagina. Endoscopic evaluation of both anterior and posterior portions of the vagina revealed a normal mucosa without scar tissue. Ultrasound examination of the cervix, uterus and ovaries did not reveal any other abnormality. The mare had a normal karyotype – 64 XX. Vestibulo‐vaginal stricture or stenosis is a congenital anomaly that occurs when there is an incomplete perforation of the hymen or occurs in association with hypoplasia of the genital canal that results in the formation of an annular fibrotic stenosis at the vestibule–vaginal junction. To our knowledge, this is the first report of vestibulo‐vaginal stricture in a mare with confirmed normal karyotype, 64, XX.